Distribution of Viral Hepatitis in Indigenous Populations of North America and the Circumpolar Arctic. Issue 3 (April 2013) - Osiowy, Carla; Brenna, C; Rempel, Julia D
The burden of viral hepatitis among indigenous populations of the United States, Canada and Greenland is greater than in non-indigenous populations. In particular, throughout the circumpolar Arctic regions, chronic hepatitis B infection is highly prevalent, although incidence rates have declined considerably in certain regions due to infant HBV vaccination. Unique HBV (sub)genotypes having distinct clinical outcomes and distribution patterns are also observed within this region. In conjunction with hepatitis B infection, hepatitis delta infection is also apparent within North American indigenous peoples, particularly with outbreaks in Greenlandic Inuit communities. Incidence rates for hepatitis C infection are higher for indigenous populations within the United States and Canada; however, some hepatitis C antibody-positive indigenous patients are more likely to be HCV RNA-negative compared to non-indigenous patients. Thus, an increased understanding of the epidemiology, clinical consequences and pathogenicity of viral hepatitis affecting the indigenous populations will help to address and balance the burden of infection.